Prosthetic reconstruction of bicuspid pulmonary valve in tetralogy of Fallot. (May 2014) - Sasikumar, Navaneetha; Ramanan, Sowmya; Rema, Krishna Manohar Soman; Kumar, Raghavannair Suresh; Subramanyan, Raghavan; Cherian, Kootturathu Mammen
Background: Various techniques have been described for preserving pulmonary valve function in tetralogy of Fallot repair. In selected substrates, the pulmonary valve can be bicuspidized and preserved using polytetrafluoroethylene pericardial membrane. Methods: This study was a retrospective review of 20 patients aged 11 months to 31 years with tetralogy of Fallot and a bicuspid pulmonary valve (with anteroposterior cusps) who underwent intracardiac repair from August 2010 to January 2013. The anterior cusp was augmented using polytetrafluoroethylene pericardial membrane to preserve the valve hinge. A transannular patch was used in all cases. Data relating to surgical outcome, intensive care unit course, pulmonary regurgitation, and right ventricular outflow tract gradient were collected. Results: There was no mortality. Predischarge pulmonary regurgitation was ≤grade 2 in 18 (90%) patients. One patient had an outflow gradient >40 mm Hg. On follow-up of 3–24 months, there was no increase in outflow gradient; 18.7% had progression of pulmonary regurgitation. Conclusion: In selected substrates, this technique is associated with minimization of pulmonary regurgitation and an excellent functional outcome. The utility of this technique needs to be validated over a longer time scale in a larger series.